Fluktuasi Populasi dan Kemunculan Imago Lalat Buah pada Perkebunan Jeruk Pamelo di Kabupaten Magetan - Ukhrowi, Syerlina Titis Muawanah; Rahmadhini, Noni; Windriyanti, Wiwin (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: The decrease in the output and quality of pomelo oranges due to improper growing methods and fruit fly pests poses a challenging control problem. The objective of this study is to ascertain the impact of abiotic influences on the variations in the population of fruit flies. Method: Observations were conducted to determine the correlation between the emergence of adult fruit flies from contaminated fruit and the population of fruit flies in the field. The study was conducted in Sukomoro District, Magetan Regency, from January - May 2024. This study integrates two techniques, explicitly using traps (Steiner traps) and host rearing. Secondary data collection encompasses gathering information on rainfall, temperature, humidity, and agriculture patterns. Results: The research findings identified two species of fruit flies in pomelo orange plantations, specifically Bactrocera carambolae and B. dorsalis. The rate of imago emergence ranges from 86% - 92%. Conclusion: each emergence is accompanied by a substantial rise in the fly population. There is no association between abiotic elements like rainfall and humidity and the changes in the fruit fly population. A statistically significant moderate correlation exists between the emergence of imago and trapped fruit flies, namely (r) of 0.616 (p) of 0.001.